2016
DOI: 10.1002/ijfe.1547
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Monetary Policy Rules for an Open Economy: Evidence from Canada and the UK

Abstract: We present an analytical framework to examine the open economy monetary policy rule of a central bank under asymmetric preferences. The resulting policy rule is then empirically examined using quarterly data with regards to Canada, and the UK from 1983q1-2007q4. Our empirical investigation shows that the open economy policy rule receives support from the data and that the monetary policy makers in the UK and Canada have asymmetric preferences. Robustness checks based on model calibration provide support for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 53 publications
3
23
0
4
Order By: Relevance
“…The other reason could be that negative and insignificant output gap implies future declines in the inflation rate, which could destabilise the economy where the interest rate approaches to lower bound. Therefore, negative output gap generate a more rigorous response than the case when the gap exceeds the assumed target [Caglayan, et al (2016)]. On the other hand, output gap seems to be positive and significant in the case of Pakistan and Sri Lanka which suggests that output exceeds the set target and demand pressure calls for the tight monetary policy in these countries, although the coefficient of output gap is less than 0.5.…”
Section: Results Of the Baseline Modelmentioning
confidence: 99%
“…The other reason could be that negative and insignificant output gap implies future declines in the inflation rate, which could destabilise the economy where the interest rate approaches to lower bound. Therefore, negative output gap generate a more rigorous response than the case when the gap exceeds the assumed target [Caglayan, et al (2016)]. On the other hand, output gap seems to be positive and significant in the case of Pakistan and Sri Lanka which suggests that output exceeds the set target and demand pressure calls for the tight monetary policy in these countries, although the coefficient of output gap is less than 0.5.…”
Section: Results Of the Baseline Modelmentioning
confidence: 99%
“…Further research will be needed to examine the drivers of monetary policy rate in non-OPEC economies in order to compare with the findings of this study. In addition, it would be an interesting area of research to examine the behaviour of monetary authorities in relation to oil price volatility by applying non-linearity assumption suggested in Caglayan et al (2016). There has been an international debate on how the central banks determine the interest rate, whether there is a rule to follow or not (rule-based monetary policy regimes vs. discretionary-based monetary policy regimes).…”
Section: Resultsmentioning
confidence: 99%
“…() and Caglayan et al . () also found that the behaviour of central banks is affected by exchange rate movements based on dynamic stochastic general equilibrium (DSGE) models.…”
Section: Literature Reviewsmentioning
confidence: 96%
See 2 more Smart Citations